Micellar poly(styrene-b-4-vinylpyridine)-nanoparticle hybrid system for non-volatile organic transistor memory - Leong, Wei Lin (2012)
We present organic field-effect transistor (OFET) memories where in-situ synthesized gold (Au) nanoparticles in self-assembled polystyrene-block-poly-4-vinylpyridine (PS-b-P4VP) block copolymer nanodomains successfully functioned as charge storage elements. Both p-type (pentacene) and n-type (perfluorinated copper phthalocyanine) OFET based memories are reported, which have stable large charge capacity and programmable-erasable properties due to charge confinement in the embedded Au nanoparticles. Optical excitation has been utilized to demonstrate photogenerated minority carrier trapping in the Au nanoparticles for efficient erasing operations. The memory devices can hence be written and read electrically and erased optically, resulting in large memory windows (9–11 V), high on/off ratio between memory states (103–105) and long retention times (>1000 s). The results clearly indicate the utility of the block copolymer-nanoparticle approach for OFET based memories.